2004
DOI: 10.1111/j.1469-8749.2004.tb00481.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver reliability of the modified Tardieu scale in the upper limb of children with hemiplegia

Abstract: This study investigated the reliability of the modified Tardieu scale in the assessment of biceps spasticity in the upper limbs of children with hemiplegic cerebral palsy (CP). Ten children, with hemiplegic CP participated in the study: six males (mean age 9 years, SD 4 years) and four females (mean age 12 years, SD 3 years). Blinded, duplicate measures of dynamic elbow extension were performed on the hemiplegic arm at time 0 and 7 days later, using the three angular velocities described in the Tardieu scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 14 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…The MTS consists of two measurements: R2 and R1 (Mackey et al, 2004). In the present study, we measured the most restricted joint motion of both the elbow and the knee.…”
Section: Modified Tardieu Scale (Mts)mentioning
confidence: 99%
See 1 more Smart Citation
“…The MTS consists of two measurements: R2 and R1 (Mackey et al, 2004). In the present study, we measured the most restricted joint motion of both the elbow and the knee.…”
Section: Modified Tardieu Scale (Mts)mentioning
confidence: 99%
“…Both parameters of the MTS have excellent intrarater and interrater reliability in children with cerebral palsy (Gracies et al, 2010). However, as with the MAS, other studies found the MTS to have insufficient reliability (Ansari, Naghdi, Hasson, Azarsa, & Azarnia, 2008;Mackey, Walt, Lobb, & Stott, 2004;Yam & Leung, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The MTS has been shown to be a valid measure of spasticity, 18 although intersessional variability in performance reduces intrarater reliability. 19 Motor performance was assessed using the QUEST for quality of movement and the Peabody Developmental Motor Scales -Fine Motor (PDMS-FM) for developmentally appropriate fine motor and upper-limb skills. The QUEST has demonstrated responsiveness in previous upperlimb BoNT-A studies.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Among the clinical scales for spasticity assessment, the Tardieu Scale represents a potential alternative to the MAS scale, as it also considers velocity-dependent characteristic of stretch reflex (Tardieu et al, 1954; Patrick and Ada, 2006). However, it is affected by operator's skills in administration, i.e., the ability to manually impose angular velocity, and by the difficulty to induce fast velocities in children (Mackey et al, 2004). Thus, its reliability is still questioned (Haugh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%